Interaction with a Kinesin-2 tail propels choline acetyltransferase flow towards synapse. - Sadananda, A.; Hamid, R.; Doodhi, H.; Ghosal, D.; Girotra, M.; Jana, S.C.; Ray, K. (Traffic, 2012)
Bulk flow constitutes a substantial part of the slow transport of soluble proteins in axons. Though the underlying mechanism is unclear, evidences indicate that intermittent, kinesin-based movement of large protein-aggregates aids this process. Choline acetyltransferase (ChAT), a soluble enzyme catalyzing acetylcholine synthesis, propagates toward the synapse at an intermediate, slow rate. The presynaptic enrichment of ChAT requires heterotrimeric kinesin-2, comprising KLP64D, KLP68D and DmKAP, in Drosophila. Here, we show that the bulk flow of a recombinant Green Fluorescent Protein-tagged ChAT (GFP::ChAT), in Drosophila axons, lacks particulate features. It occurs for a brief period during the larval stages. In addition, both the endogenous ChAT and GFP::ChAT directly bind to the KLP64D tail, which is essential for the GFP::ChAT entry and anterograde flow in axon. These evidences suggest that a direct interaction with motor proteins could regulate the bulk flow of soluble proteins, and thus establish their asymmetric distribution.